Design and Implementation of Object Tracking System Using Smart Phones - Jose, Albin S; Sreekumar, Anoop R.S (International Journal of Computer Sciences and Engineering, 2025)
To find out the location of unknown area, user need to call and ask some others where they are. In “Internet and computer Geo-Location tracking” the user can be tracked by the tracker by providing the IP address. But “Tracking using GPS in smart phones” helps user to find out the location of the person with the mobile number. “Tracking using GPS in smart phones” uses a mobile application based on providing Location Based Services (LBS) using Global Positioning System (GPS) as a location provider. This application offers the service to get users current location and shows the same on Google Map. The location is updated when the user moves from one place to another. The main objective of this work is to design and implement a client server system that helps users to locate their family members and receive alerts